The potential of disability experience for heritage. - Negin Eisazadeh; Ann Heylighen; Claudine Houbart (Ochrona Dziedzictwa Kulturowego, 2023)
The relation between accessibility and conservation is often contested, resulting in tensions between accessibility advocates and heritage experts. While the importance and necessity of accessibility and gradually the broader notion of inclusivity for diverse users (e.g. disabled people) is becoming more evident, existing discussions mainly focuses on the issues and problems of accessibility in the heritage context. In this article, instead of focusing on the constraints, we present disability experience as a generative resource rather than hindering liability.